Modification of Dielectric Strength of Iraqi Kaolin by the Addition of Micro and Nano Zirconia (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Iraqi kaolin as a matrix material is used as a principle part of the study after additives sugarcane straw in ratio (10%) and (2%) Poly Vinyl Alcohol ( PVA) as a binding material. (Micro or Nano) Zirconia has been added to the composite in different ratio ( 0% , 5 % , 10% , 15% , 20%) for the purpose of improving thermal properties. Samples are formed in a semi-dry  pressing with pressure of about (25 Mpa).    The formulation is achieved by using a template  of (12 mm) diameter and a time of about (2 min). Then, the prepared samples have been sintered.   Burning process was carried out by three temperature degrees ( 1000, 1100, 1200 ) Co for mean raise about 3 temperature degree / 1 minute and remained at every temperature degree for two hours.    The results showed that the increase in the proportion of ( Micro or Nano ) Zirconia results in increasing the value of dielectric strength and the best results were achieved by adding Nano Zirconia. The increasing of the burning temperature also leads to increase in the value of the dielectric strength.